Analisis Kemampuan Pemecahan Masalah Pola Bilangan Ditinjau Dari Gaya Belajar - I Gusti Ayu Sinta Inastuti; Sri Subarinah; Eka Kurniawan; Amrullah Amrullah (Griya Journal of Mathematics Education and Application, 2021)
The purpose of this study was to determine eighth grade student problem-solving ability on number pattern material. This study was held academic year focused on assessing students learning styles. The methods used in this study were questionnaires, tests, and interviews. The results showed that class VIII students consisted of 26 students had visual learning styles, 24 students had auditory styles and 16 students had kinesthetic styles. Subjects taken in this study were 2 students from each learning style, then the subject was given a test to describe the number pattern material and conducted an interview. As a result, based on the analysis of the problem-solving ability stages, students with visual and auditory learning styles were able to reach the stage of understanding the question / problem, designing and choosing a solution strategy, and solving problems with a mathematical model, but have not yet reached the stage of re-checking the solutions obtained. On the contrary, Students with a kinesthetic learning style have been able to reach the stage of understanding the question / problem, but have not been able to reach the stage of designing and choosing a solution strategy, or solving problems with mathematical models, and even re-checking the solutions obtained. This shows that the problem solving ability of students with visual and auditory learning styles is better than students with kinesthetic learning styles.